The Investigation of Heavy Metal Content (Cu, Cd, Pb) in Sapu-Sapu Fish (Hypostomus plecostomus) in Bengawan Solo River - Setyarini, Ristiyana Eko; Astuti, Dwi; Ambarwati, A (Universitas Muhammadiyah Surakarta, 2005)
A study had been carried out to investigate heavy metal (Cu, Cd, Pb) content in sapu-sapu fish (hypostomus plecostomus) in Bengawan Solo river. The type of this research was observational research, with sapu-sapu fish inhabit Bengawan Solo River as the population. The samples were taken with purposive random sampling. Nine sapu-sapu fishes taken from 3 places, i.e.: Nguter Sukoharjo area, Premulung river outlet and Anyar river, 3 fishes from each palce, and then take examined the content of heavy metal. The result of study showed that the average content of Cu: 0.027 mg/100gr, Cd: 0.005 mg/100gr and Pb: 0.042 mg/100gr. Hence, sapu-sapu fish in Be3ngawan Solo had been contaminated with heavy metal (Cu, Cd, and Pb) and should not be consumed.